(3aJM GdeZjK HTQM CdajI GdMOjKs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s; (3GHf GdYQGbj , CMeO Hf YHO GdQMje Hf GdMSjf GdYQGbj GdTGaYj,J (B826 (3g` s
(3ChdgG (B:s
(3hHYO aYde GdMOjK NWjQ hbYg cKjQ faYg Ydjg eOGQ CcKQ GdCMcGe hHg JYQa GdMdGd hGdMQGe s
(3BNQgG (B:s
(3Ch HYVgG Cf jQhj Yfj LejY gPG GdTQM YdjgG hLejY eG jLhR dj QhGjJg hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs